Paternal attachment, negative life events, automatic thoughts and depressive symptoms of adolescents in Peninsular Malaysia - Yahya, Amira Najiha; Zulkefly, Nor Sheereen; Baharudin, Rozumah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Depressive symptoms are major public health issues with significantly increasing rates during adolescence. Specific factors and mechanisms associated with depressive symptoms still need to be identified. The present study aimed to examine direct relationships between paternal attachment and negative life events (NLE) to depressive symptoms. Indirect effect of automatic thoughts on the relationships was also examined. Methods: A sample of 1030 adolescents aged between 13 and 19 years (mean=15.36) was recruited using probability proportional to size cluster sampling from selected states in Peninsular Malaysia to complete self-report measures on the study variables. Results: Structural equation modelling indicated that paternal attachment in terms of secure, approachability and anxious fearful were directly associated to depressive symptoms. Broadly, increases in secure and approachability attachments followed by decreases in depressive symptoms. Adolescents who experienced anxious fearful attachment seemed to be more vulnerable to depressive symptoms. Moreover, results from mediation analyses revealed that automatic thoughts mediated the effect of two attachment variables (i.e., anxious fearful and responsiveness) and NLE to depressive symptoms. Conclusion: These findings shed light on the concurrent effects of attachment and life events on depressive symptoms, providing evidence on how to reduce depressive symptoms among adolescents. The current study also expands knowledge on the role of automatic thoughts as potentially relevant mediator. Intervention and prevention programs aimed at preventing adolescents from the deleterious effects of depressive symptoms should involve both parents and adolescents in order to promote optimal attachment relationships and minimize depressive cognitions in adolescents.